PENGARUH PROGRAM GREEN ECO LIFESTYLE GREEN RADIO 96,7 FM TERHADAP GAYA HIDUP PEDULI LINGKUNGAN PADA MASYARAKAT KOTA PEKANBARU - Lubis, Laila; Rasyid, Anuar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The mass media has a role in conveying information to the public and fulfilling the need for entertainment for the community. One of the mass media that has this role is radio. Green Radio 96.7 FM presents the Green Eco Lifestyle Program that addresses topics of environmental care that are packaged in a relaxed, fun and informative manner. The Green Eco Lifestyle program aims to invite and change the lifestyle of listeners more concerned about the environment. The theory used in this study is the Stimulus-Response theory.This study aims to find out how much the audience's response to the Green Eco Lifestyle Green Radio 96.7 FM Program is to find out how much the listeners respond to the environmentally caring lifestyle in the people of Pekanbaru City and to analyze the influence of the Green Eco Lifestyle Green Radio 96.7 FM Program towards environmental care for the people of Pekanbaru City. This type of research is quantitative research with descriptive and explanatory methods using purposive sampling technique and the Unknown Population formula obtained 100 respondents. Researchers collected data through questionnaires while for data analysis techniques researchers used descriptive analysis techniques and inferential analysis techniques with simple linear regression formula.The results of this study indicate that the level of influence of the Green Eco Lifestyle Program on the Environmental Care Lifestyle for the people of Pekanbaru City is very weak. This is seen from the simple linear regression in this study is Y = 6.749 + 0.537 X. Meanwhile, t count 4.730 is greater than the t table of 1.984 with a significance level of 0.000 smaller than that of Î± = 0.05. Based on the table "Model Summary" shows that the value of R = 0.431 and the coefficient of determination (R square) is equal to 0.186. This figure shows the understanding that the influence of the Green Eco Lifestyle Program on the Environmental Care Lifestyle for the people of Pekanbaru City is 18.6%. While the remaining 81.4% is again influenced by other variables not included in this study.